Novel Drosophila melanogaster genes encoding RRM-type RNA-binding proteins identified by a degenerate PCR strategy. - Brand, S.F.; Pichoff, S.; Noselli, S.; Bourbon, H.M. (Gene, 1995)
We are interested in identifying Drosophila melanogaster RNA-binding proteins involved in important developmental decisions made at the level of mRNA processing, stability, localization or translational control. A large subset of the proteins known to interact with specific RNA sequences shares an evolutionarily conserved 80-90-amino-acid (aa) domain referred to as an RNA-recognition motif (RRM), including two ribonucleoprotein identifier sequences known as RNP-1 and RNP-2. Hence, we have herein applied degenerate polymerase chain reaction (PCR) methodology to clone three additional members (termed rox2, rox8 and rox21) of the D. melanogaster RRM-protein gene superfamily encoding putative trans-acting regulatory factors. Representative cDNA clones were isolated, the conceptual aa sequences of the candidate Rox proteins were inferred from their nucleotide sequences, and database searches were conducted. Rox2 displays extensive aa sequence similarities to putative RNA-binding proteins encoded by the genomes of the plants Oryza sativa and Arabidopsis thaliana; Rox21 resembles essential metazoan pre-mRNA splicing factors; as described elsewhere, Rox8 is likely a fly homolog of the two human TIA-1-type nucleolysins [Brand and Bourbon, Nucleic Acids Res. 21 (1993) 3699-3704].